Grain refinement in a metastable beta Ti alloy deformed to large strains at high strain rates. (15th September 2018) - Zafari, A.; Xia, K.
Abstract: Shear punching to large plastic strains up to 40 was conducted on a metastable β Ti alloy at various speeds, creating severe plastic deformation at high shear rates ( γ ˙ ) up to 200 s −1 . Grain refinement in the resulting shear bands (SBs), which experienced even faster deformation due to strain localisation, was studied using extensive TEM. Significant grain refinement occurred at γ ˙ < 40 s −1, producing β grains of ∼5–10 nm, considerably smaller than those obtained by high pressure torsion (HPT) to a much higher strain of 240 at a slow shear rate of 0.5 s −1 . The applied shear strain rate of 2 s −1 was found to be an optimum for attaining a pure nano-β grain structure thanks to maximum dislocation activity and complete α" to β reverse transformation. However, some stress induced α" remained as γ ˙ deviated from this value and much coarser β grains formed at γ ˙ > 40 s −1 . The effects of strain rates on grain refinement and the minimum achievable grain sizes at high strain rates are discussed based on classical dislocation dynamics. Graphical abstract: Image 1